ANALISIS PERILAKU NARSISME PADA PESERTA DIDIK KELAS XII MIPA MAN 2 PONTIANAK TAHUN 2019 - Pratiwi, Rani Diah; Asrori, Muhammad; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractNarcissism is a behavior characterized by a tendency to look at himself in an excessive way, love to boast about himself and expect others to give praise, besides that embedded in him the feeling of the most capable, most unique (different himself) and feel special compared to others. Basically narcissism is a form of self-actualization of someone who loves himself excessively. The term narcissism in psychology can be classified as a personality disorder. The general problem in this research is How is Narcissism Behavior Analysis in Class XII MIPA MAN 02 Pontianak Year 2019? The sub-problems are (1) What are the characteristics of narcissistic behavior in class XII MIPA MAN 2 Pontianak students in 2019? (2) What are the factors that cause narcissism behavior in students of class XII MIPA MAN 2 Pontianak in 2019? (3) What are the effects of narcissistic behavior on students of class XII MIPA MAN 2 Pontianak in 2019? (4) Are the efforts made by the guidance and counseling teacher in helping to overcome narcissistic behavior in students of class XII MIPA MAN 2 Pontianak in 2019? The method used is descriptive method, and the form of research is a survey study. The population in this study was the Analysis of Narcissism Behavior in MAN 2 Pontianak 2019 MIPA Students. This research uses quantitative research. Data collection techniques are indirect communication techniques while the data collection tool is a questionnaire. Data analysis techniques using the percentage formula Based on the results of this study indicate that Narcissism Behavior Analysis in Students of Class XII MIPA MAN 2 Pontianak is in the "High" category. Based on the description above, in general it can be concluded that the Analysis of Narcissism Behavior in Students of Class XII MIPA MAN 2 Pontianak as a whole obtains the category of "High".Â Keywords: Narcissism Behavior, StudentsÂ